A questionnaire for measuring presence in virtual environments: factor analysis of the presence questionnaire and adaptation into Brazilian Portuguese. Issue 4 (November 2016) - Silva, Gustavo; Donat, Júlia; Rigoli, Marcelo; Oliveira, Fernando; Kristensen, Christian
Abstract The increasing use of virtual reality (VR) environments in different domains of research and psychotherapy offers advantages over traditional treatment approaches. However, in order to feel immersed and involved by the VR experience, participants require VR scenarios that promote the subjective feeling of "being there, " i.e., presence. The most utilized mean of operationalization of presence is through self-report scales and questionnaires. This article aims to report the translation and adaptation of the presence questionnaire (PQ) into Brazilian Portuguese, comparing the factorial distribution of the adapted version with the original PQ. Translation and back-translations were conducted by a team of Brazilian psychologists and computer science professionals with experience on the field. Participants (n  = 100) answered the Brazilian version of the questionnaire after wearing a head-mounted display (HMD) and driving a virtual automobile in a VR scenario. The principal component analysis of the translated version generated factors consistently with the original study; however, items that had equivocal construct adequacy in the original PQ changed factors. The factor structure of the PQ is discussed. The growing use of VR environments requires instruments assessing the presence of immersed individuals, and the Brazilian Portuguese version of the PQ appears to be a viable option.